2023
DOI: 10.3390/ijms24087407
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus and Multiple Sclerosis: A Convoluted Interaction and the Opportunity to Unravel Predictive Biomarkers

Abstract: Since the early 1980s, Epstein-Barr virus (EBV) infection has been described as one of the main risk factors for developing multiple sclerosis (MS), and recently, new epidemiological evidence has reinforced this premise. EBV seroconversion precedes almost 99% of the new cases of MS and likely predates the first clinical symptoms. The molecular mechanisms of this association are complex and may involve different immunological routes, perhaps all running in parallel (i.e., molecular mimicry, the bystander damage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 107 publications
0
2
0
Order By: Relevance
“…It has been calculated that the risk of MS is more than 20-fold higher if HLA-DRB1*1501 is present in combination with high titers of EBNA-1 antibodies [ 40 ]. Furthermore, recent studies have observed that EBV, through the utilization of specific virulence factors, may possess the ability to manipulate MS susceptibility genes via epigenetic regulation [ 102 ].…”
Section: Msmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been calculated that the risk of MS is more than 20-fold higher if HLA-DRB1*1501 is present in combination with high titers of EBNA-1 antibodies [ 40 ]. Furthermore, recent studies have observed that EBV, through the utilization of specific virulence factors, may possess the ability to manipulate MS susceptibility genes via epigenetic regulation [ 102 ].…”
Section: Msmentioning
confidence: 99%
“…Additionally, studies on the noncyclic nucleoside analogue tenofovir alafenamide have revealed its ability to inhibit EBV DNA polymerase. Based on these findings, a clinical trial is currently underway to assess the use of this drug as an add-on to ocrelizumab, evaluating its efficacy in alleviating MS symptoms and promoting neuroprotection [ 102 ].…”
Section: Msmentioning
confidence: 99%